Implementing community based inclusive development for people with disability in Latin America: a mixed methods perspective on prioritized needs and lessons learned - Andreas Bachfischer; Martha Cecilia Barbosa; Angel Alberto Riveras Rojas; Reinaldo Bechler; Eva-Maria Schwienhorst-Stich; Christa Kasang; Anne Simmenroth; Sandra Parisi (International Journal for Equity in Health, 2023)
Abstract Background Research on the needs of people with disability is scarce, which promotes inadequate programs. Community Based Inclusive Development interventions aim to promote rights but demand a high level of community participation. This study aimed to identify prioritized needs as well as lessons learned for successful project implementation in different Latin American communities. Methods This study was based on a Community Based Inclusive Development project conducted from 2018 to 2021 led by a Columbian team in Columbia, Brazil and Bolivia. Within a sequential mixed methods design, we first retrospectively analyzed the project baseline data and then conducted Focus Group Discussions, together with ratings of community participation levels. Quantitative descriptive and between group analysis of the baseline survey were used to identify and compare sociodemographic characteristics and prioritized needs of participating communities. We conducted qualitative thematic analysis on Focus Group Discussions, using deductive main categories for triangulation: 1) prioritized needs and 2) lessons learned, with subcategories project impact, facilitators, barriers and community participation. Community participation was assessed via spidergrams. Key findings were compared with triangulation protocols. Results A total of 348 people with disability from 6 urban settings participated in the baseline survey, with a mean age of 37.6 years (SD 23.8). Out of these, 18 participated within the four Focus Group Discussions. Less than half of the survey participants were able to read and calculate (42.0%) and reported knowledge on health care routes (46.0%). Unemployment (87.9%) and inadequate housing (57.8%) were other prioritized needs across countries. Focus Group Discussions revealed needs within health, education, livelihood, social and empowerment domains. Participants highlighted positive project impact in work inclusion, self-esteem and ability for self-advocacy. Facilitators included individual leadership, community networks and previous reputation of participating organizations. Barriers against successful project implementation were inadequate contextualization, lack of resources and on-site support, mostly due to the COVID-19 pandemic. The overall level of community participation was high (mean score 4.0/5) with lower levels in Brazil (3.8/5) and Bolivia (3.2/5). Conclusion People with disability still face significant needs. Community Based Inclusive Development can initiate positive changes, but adequate contextualization and on-site support should be assured.